Red Guard Movement in the First Years of “Cultural Revolution” in China (1966—1967): View of Domestic and Foreign Researchers - V. V. Bondareva (Научный диалог, 2020)
The article analyzes the first years of “the cultural revolution” in China (1966—1967), characterized by high revolutionary activity of students and school youth, organized into groups of “red guards”, who were distinguished in their actions by extreme cruelty and fanaticism. From this point of view, the destructive actions of the red guards, which were of a terrorist and mass nature, highlight the main direction of their revolutionary strike, which was inflicted on the party and state apparatus of China. Mao Zedong is presented as the initiator of a mass movement of red guards who used monstrous terrorist methods to fight his opposition and all, from their point of view, not enough politically conscious elements. The hongweibing movement, considered as an instrument of Mao Zedong’s struggle with the opposition, allows to reveal in the course of research the personal qualities of a leader who, in the name of establishing his own cult, was not afraid to deliberately plunge the entire country into mass and deeply disorderly turmoil. The detailed description of Mao Zedong’s personal attitude to what is happening, based on documentary sources, reveals the deeply dictatorial and anti-democratic nature of his power, which was asserted in the first years of “the cultural revolution” with the help of the red guards movement.